FLYPAPER EFFECT BELANJA DAERAH TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI PROVINSI ACEH - Nurul Chadiza; Sofyan Syahnur (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2022)
Abstract This study aims to analyze the flypaper effect of regional expenditure on District/City Economic Growth in Aceh Province. The data in this study uses secondary data in the form of annual data from 2008 to 2020 obtained from BPS, DJPK and the Ministry of Finance. The type of data used in this study is panel data, which consists of Time Series data in the form of annual data from 2008-2020 and Cross Section data in the form of Regency/City data in Aceh Province. The model used in this study is Path Analysis. The conclusion of this study is that simultaneously PAD, DAU, DBH, DAK have a significant effect on regional spending. Partially PAD, DAU, DAK have a positive effect on regional spending. Partially or simultaneously PAD, DAU, DBH, DAK, BD have a significant effect on economic growth. There is no flypaper effect in the District/City of Aceh Province. Keywords: Flypaper effect, regional expenditure, economic growth.